Assessment of utilization and willingness to use it devices to support health management - Espírito-Santo, Margarida (2021)
Background Amongst the technological solutions that aim to facilitate daily tasks, the potential contributions of mhealth is significant, mainly within the crescent elderly population presenting chronic diseases and using medication. Thus, this study aimed to assess the utilization and willingness to use IT devices to support health management, such as medication management. Methods A cross-sectional study was held, including the application (face-to-face and online) of an electronic questionnaire, with 164 participants. Data were processed using SPSS v27. Results Study participants had a mean age of 37.6 ± 20.0 years old, 23.8% were ≥ 60 years old, 73.2% female, 28% declared to suffer a chronic disease, with 27.4% using chronic medication and mostly managed by oneself (71.1%). Most of the participants owned and used a mobile phone (respectively 93.9% and 59.8%), a tablet (48.8% and 44.5%), and a computer (73.8% and 17.1%). Only about half of the participants aged ≥ 60 years declared to use their mobile devices to internet access (mobile phones 51.3%, tablet 35.9% and computers 41%). In this group, only 2% mentioned using applications in the health area. Overall, 85.4% considered these tools could be useful, although fewer would be willing to buy them (33.6% for < 60 years and 66.7% for ≥ 60 years). Conclusions The use of IT devices is less widespread in the older population, the age groups with greatest need for tools to support health management. Future development of this area must pay special attention to target audience characteristics and their limitations in the use of technology.